Структурно-словотворчі особливості англійських топонімів - Орлова, С. І.; Orlova, S. I. (Східноєвропейський національний університет ім. Лесі Українки, 2011)
У статті охарактеризовано топоніми як факти мови, які закріплені територіально, що є джерелом історії народу, його мови. Окреслено проблеми системності топонімії, компонентного аналізу топонімів, їхньої форми та змісту. Описано структурні моделі англійських топонімів. In this article toponyms are facts of the language which are hailed to the particular territory. It was determined that toponyms are the source of people’s history and its language. This article deals with the problem of analysis of toponyms according to their components and context. Structural models of ancient English toponyms were described.
Structural and Word-Formative Peculiarities of English Toponyms
Keywords: топонім; системність топонімії; структурні моделі англійських топонімів; компонентний аналіз топонімів; форма топоніма; зміст топоніма; toponym; the problem of toponyms as the system; structural models of ancient English toponyms; analysis of toponyms according to their components; the form of a toponym; the context of a toponym